Cannibalism and its importance in Aquaculture: A review - Hetényi, Zoltán László; Molnár, Péter István; Bársony, Péter; Fehér, Milán (Acta Agraria Debreceniensis, 2025)
Intracohort cannibalism may lead to significant losses during the early life stages of farmed fish. The mechanisms driving cannibalism dynamics are common across many fish species and are closely linked to the factors that influence growth variation within a population. This genetically encoded behaviour allows the individual to eliminate competitors in the competition for resources and increases the chances of survival and reproduction. Many fish species display aggression towards individuals of the same species, which can often lead to cannibalistic behavior. This foraging strategy is also present in intensive aquaculture systems, and its economical, ecological and phylogenetic implications have been debated by many researchers. Many fish species can be produced economically in recirculation aquaculture (RAS) systems, but the efficiency of larval and juvenile rearing remains a bottleneck for most species. The success of initial rearing depends on many factors. In addition to genetic factors, the level of cannibalism is mainly influenced by the applied production and feeding technology. Literature suggests that mortality during larval rearing can be as high as 50%, largely due to aggression. In the case of predatory fish species, the presence or absence of certain husbandry conditions can lead to even higher levels of cannibalism, which significantly reduces production yields by causing mortality and secondary injuries, thus further decreasing the survival rate. This review therefore aims to identify and quantify the effects of biotic and abiotic factors that influence cannibalism.